(untitled) (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2023)
Artificial intelligence and the blues of its legal regulation This article discusses the origin, history and legal issues related to the concept of artificial intelligence. We will talk about its place in the history of mankind, the trends of world progress. It is noted that artificial intelligence has taken a special place in the context of the growing capabilities of computer and information technologies. The factors of the need for artificial intelligence are analyzed, provided that the scope of artificial intelligence is expanding day by day. Also, what is the legal recognition of the use of modern information technologies that create artificial intelligence, how the copyright for artificial intelligence products is formalized, these issues will be discussed in detail in this article.